2018
DOI: 10.1177/0333102418804161
|View full text |Cite
|
Sign up to set email alerts
|

Correlations among brain and spinal MRI findings in spontaneous intracranial hypotension

Abstract: Objectives Several brain and spinal magnetic resonance imaging signs have been described in spontaneous intracranial hypotension. Their correlations are not fully studied. This study aimed to explore potential mechanisms underlying cerebral neuroimaging findings and to examine associations among spinal and brain magnetic resonance imaging signs. Methods We conducted a retrospective review of magnetic resonance myelography and brain magnetic resonance imaging records of patients with spontaneous intracranial hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…Spinal MRI can demonstrate various secondary spinal manifestations of IHS like ISFCs, dilated veins, and dural enhancement [2]. Supratentorial changes, as, for example, subdural hygromas, that are usually included into follow-up examination to ascertain regression are increasingly complemented by spinal imaging as well [18]. Since repeated or chronic microbleeds in IHS cases with an associated ISFC can lead to complications like SS [23] with potentially irreversible neurological deficits, spinal imaging rightfully deserves our attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal MRI can demonstrate various secondary spinal manifestations of IHS like ISFCs, dilated veins, and dural enhancement [2]. Supratentorial changes, as, for example, subdural hygromas, that are usually included into follow-up examination to ascertain regression are increasingly complemented by spinal imaging as well [18]. Since repeated or chronic microbleeds in IHS cases with an associated ISFC can lead to complications like SS [23] with potentially irreversible neurological deficits, spinal imaging rightfully deserves our attention.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, failure in leakage closure and ISFC resorption may lead to irreversible structural lesions of the central nervous system. The efficacy of the blood patches or surgery was often correlated to the reversal of cerebral abnormalities [15,16]; however, more recently spinal alterations have become the focus of attention as well [17,18]. The aim of the following study was to clarify the association of clinical disease activity with regard to persistence or regression of ISFC in chronic IHS and to study long-term sequels with regard to the occurrence of a cerebral hemosiderosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations reported that several predictors are thought to be related to the disease severity and treatment outcomes, for instance, pontomesencephalic angle and the angle between the vein of Gallen and the straight sinus (Fig. C) . By combining the CT and MRI findings, clinicians could reach more sensitive differential diagnosis of SIH.…”
Section: Discussionmentioning
confidence: 99%
“…4C). 36,37 By combining the CT and MRI findings, clinicians could reach more sensitive differential diagnosis of SIH. Second, there might be a selection bias since only those patients who were admitted to our institution presenting with bilateral subdural fluid collections were enrolled.…”
Section: Discussionmentioning
confidence: 99%
“…Brain tissue volume, however, is generally considered invariable, and therefore, compensation would occur through an increase of blood volume, specifically venous blood, since veins are more adjustable than arteries (1). Prior studies have reported deformities of certain brain structures in SIH patients (15,20,21), and therefore, whether total brain tissue volume is invariable remains unknown. The primary aim of the current study was to evaluate whether brain tissue volume is fixed or variable in SIH patients using automatic quantitative methods.…”
Section: Introductionmentioning
confidence: 99%